Measurement of Dissipation Factor of Inner Layers of Insulation in Three-Core Belted Cables - Kostiukov, Ivan Oleksandrovich (Національний університет міського господарства імені О. М. Бекетова, 2021)
This paper presents a substantiation of an approach for direct measurements of dielectric dissipation factor of layers of insulation between the conductors of three-core power cables. Proposed approach is based on grounding of the inspected dielectric layer through the sufficiently low electrical resistance. The results of carried out analysis, which was carried out taking into consideration the presence of numerous parasitic parameters of tested layer of insulation due to the capacitive coupling between the electrically conductive elements of three-core power cable, have shown that for the case of sufficiently low value of used resistor the value of phase shift between the waveforms of voltage drop on inspected layer of insulation and resistor, through which this layer of insulation is grounded, coincides with the value of phase shift between the sine waveforms of current and voltage for parallel equivalent scheme of tested layer of insulation with power losses. Because of the dependence of dielectric power loss angle on the value of phase shift between sine curves of current and voltage, the presented approach for the measurement of dielectric dissipation factor is based on such coincidence of values of phase shift. Depending on the value of applied resistor, the value of dissipation factor is calcu lated on the basis of measured value of phase shift between the voltage drop on the electrical resistor, through which tested layer of insulation is grounded, and either the waveform of voltage drop on the inspected layer of insulation, or the waveform of applied voltage. Factors that affect the accuracy of measurement are discussed, equivalent schemes of tested three core power cable for various ways of applying testing voltage are presented and the example of practical implementation of presented approach for dissipation factor measurement is also given. Further development of presented approach for dissipation factor measurement is supposed to include the comparative analysis of the results of its practical implementation with the results obtained by applying previously developed techniques based on aggregate measurements

У статті представлено обґрунтування підходу до прямого вимірювання тангенса кута діелектричних втрат шарів ізоляції між жилами трьохжильних силових кабелів. Запропонований підхід заснований на заземленні досліджуваного шару ізоляції через достатньо низький електричний опір. Результати аналізу, проведеного з урахуванням наявності численних паразитарних параметрів досліджуваного шару ізоляції внаслідок ємнісних зв'язків між електропровідними елементами конструкції трьохжильного силового кабелю, показали, що для випадку достатньо низького значення електричного опору використаного резистора значення фазового зсуву між напругою на досліджуваному шарі ізоляції та резисторі, через який цей шар ізоляції заземлено, збігається зі значенням фазового зсуву між синусоїдальними кривими струму та напруги для паралельної схеми заміщення досліджуваного шару ізоляції з діелектричними втратами. Внаслідок залежності кута діелектричних втрат від величини фазового зсуву між струмом та напругою, представлений підхід до вимірювання тангенса кута діелектричних втрат базується на зазначеному збігу значень фазового зсуву. В залежності від величини використаного резистора, значення тангенса кута діелектричних втрат обчислюється на основі виміряного значення фазового зсуву між падінням напруги на електричному резисторі, через який заземлено досліджуваний шар ізоляції, та між падінням напруги на досліджуваному шарі ізоляції, або між прикладеною до силового кабелю напругою. В статті також обговорено фактори, що впливають на точність вимірювань, запропоновано схеми заміщення досліджуваного трьохжильного силового кабелю для випадку різних способів подачі випробувальної напруги та наведено приклад практичної реалізації представленого підходу для вимірювання тангенса кута діелектричних втрат. Подальший розвиток представленого підходу до вимірювання тангенса кута діелектричних втрат повинен містити порівняльний аналіз результатів його практичної реалізації з результатами, отриманими шляхом застосування раніше розроблених та заснованих на сукупних вимірюваннях методик.
Вимірювання тангенса кута діелектричних втрат внутрішніх шарів ізоляції в трьохжильних кабелях з поясною ізоляцією
Keywords: Cross-Correlation; Electrical Capacitance; Insulation Deterioration; Insulation Testing; Phase Shift; Diagnostics of Power Cables; Dielectric Power Losses; взаємна кореляція; електрична ємність; старіння ізоляції; випробування ізоляції; фазовий зсув; діагностика силових кабелів; діелектричні втрати